Development of a 3D printed paranasal sinus system prototype for endoscopic surgery training (Transactions on Additive Manufacturing Meets Medicine, 2024)
Functional endoscopic sinus surgery (FESS) stands as a crucial treatment method in otolaryngology, necessitating sophisticated training models for effective skill acquisition. Addressing this need, an additively manufactured prototype of the paranasal sinus system for endoscopic training was developed. Critical to in the development process was the identification and integration of tissue-equivalent materials simulating mucosa, cartilage, and bone tissue. A comprehensive AM material evaluation encompassing multiple iterations was conducted, focusing on haptic fidelity and visual resemblance. A training environment with an excess through the left nostril was produced using fused deposition modeling (FDM) printing as well as stereolithography (SLA). Ultimately, a flexible resin, crafted through SLA printing, and a silicone mixture emerged as the optimal choice for mimicking the anatomical structure of the paranasal sinus system. By carrying out various operation steps of the FESS, practitioners were able to assess the suitability of the prototype and, in particular, the materials used. While overall feedback was positive, refinement opportunities, notably regarding mucosal thickness, were identified. Looking ahead, insights gained from this additive manufactured training model could be used to develop of a comprehensive training model tailored to clinical needs.
Keywords: medical training; 3D printing; Paranasal Sinus System; Functional endoscopic sinus surgery